Computers and information systems - Hutchinson, Sarah E.; Sawyer, Stacey C. (Boston, Mass. : Irwin/McGraw-Hill, 1996)
Input hardware. Processing hardware. Storage hardware. Output hardware. Software. Software development and programming languages. Communications and connectivity. Systems development. Database management...
Keywords: Information storage; Retrieval systems; Computer software; Computers; Database management; Computers; Computer software; Information storage and retrieval systems